Kebudayaan dalam Pandangan Iman Kristen - Agustina Hutagalung; Benny Christian Hutabarat; Anton Sitorus; Ratna Saragih; Arif Sitompul (Berkat : Jurnal Pendidikan Agama dan Katolik, 2025)
Culture is an integral part of human life, reflecting the capacity as creatures made in the image of God. This article explores the relationship between Christian faith and culture from theological and biblical perspectives. The discussion covers the meaning and essence of culture, the origin of culture according to the Bible, as well as challenges and issues in integrating culture and Christian faith. Additionally, this article provides a critical analysis of the relevance of the Gospel in the context of modern culture, accompanied by case studies of churches in Indonesia. By understanding culture as a redeemable blessing from God, the church has a responsibility to bring transformation to society without compromising the integrity of the Gospel.